THE IMPACT OF CARBON , NITROGEN SOURCES AND METALSALTS ON PRODUCTIVITY OF CAROTENE SYNTHESIZING STRAINS BACILLUS SUBTILIS 1.1 AND B. AMYLOLIQUEFACIENS UCM B-5113 - О. О. Нечипуренко (Mìkrobìologìâ ì Bìotehnologìâ, 2015)
Puspose. To investigate the impact of carbon, nitrogen sources and metal salts on the productivity of carotene synthesizing strains B. amyloliquefaciens UCM B-5113 and B. subtilis 1.1. Methods. The features of growth and pigment production of investigated strains were determined by submerged cultivation in periodic conditions based on biotechnology parameters. The pigments extraction was carried out with the use of mixture of chloroform and methanol (2:1). The qualitative composition of carotenoids was assessed by their absorption spectra. Results. The highest total carotenoids productivity of strains B. amyloliquefaciens UCM B-5113 and B. subtilis 1.1 was on the media containing arabinose, maltose, (NH4)2SO4 and FeSO4 and composed 168 and 384 mg/l, 310 and 570 mg/l, 296 and 640 mg/l, 309 and 605 mg/l, respectively. Conclusion. Arabinose, maltose, (NH4)2SO4 and FeSO4 were the optimum sources of carbon, nitrogen and metal salts for growth and carotenoids synthesis by investigated Bacillus strains. Overall productivity of strains B. subtilis 1.1 and B. amyloliquefaciens UCM B-5113 was higher than on control medium at 2.1–3.9, and 1.6–2.7 times, respectively, with constant quality of pigment composition.